Equine herpesvirus myeloencephalopathy - TGW, Teodoro; FS, Mendonça; J, Asin (Brazilian Journal of Veterinary Pathology, 2023)
A euthanized, 14-year-old, Warmblood gelding that had participated in an equine show was presented for necropsy and diagnostic workup to the San Bernardino laboratory of the California Animal Health and Food Safety Laboratory System. The animal had a 4-day history of mildly swollen limbs and hyperthermia, and developed neurologic signs shortly before euthanasi